Assessing political second screening behavior and personality traits: The roles of economic development, freedom of expression and monochromatic vs. polychromatic cultures. (June 2020) - Huber, Brigitte; Gil de Zúñiga, Homero; Liu, James
Highlights: Two-wave panel data from 19 countries worldwide. Extraverted people tend to second screen more than introverts do. Agreeableness and openness are negatively related to second screening. Economic, political and cultural indicators explain differences between countries. Abstract: This study focuses on an emerging media multitasking phenomenon called second screening or dual screening. Employing two-wave panel-data from 19 countries, we test whether the Big Five personality traits help explain the use of an additional screen or device while watching political content on TV to discuss the program with others or to look up for additional information. Results show that extraversion positively predicts political second screening. In contrast, agreeableness and openness to new experience are negatively related to political second screening. Moreover, multilevel analysis is performed to test whether the between-country variation is related to economic, political and cultural indicators.